English Teachers as materials developers - Ramírez Salas, Marlene (Universidad de Costa Rica, 2004)
Este artículo enfatiza la necesidad de que los profesores de Inglés crean y adapten sus propios materiales. La autora presenta la definición de Desarrollo y Adaptación de Materiales, su proceso y algunos ejemplos elaborados por ella misma para ilustrar el tema. This article focuses on the need for English language teachers to become materials developers.  The writer presents a definition of Materials Development and Adaptation, the process to follow to develop and/or adapt teaching materials, and some samples created or adapted by the writer to illustrate the topic.